Beta-Blocker Therapy Is Associated With Increased 1-Year Survival After Hip Fracture Surgery: A Retrospective Cohort Study. (November 2021) - Mohammad Ismail, Ahmad; Ahl, Rebecka; Forssten, Maximilian Peter; Cao, Yang; Wretenberg, Per; Borg, Tomas; Mohseni, Shahin
Abstract : BACKGROUND: The high mortality rates seen within the first postoperative year after hip fracture surgery have remained relatively unchanged in many countries for the past 15 years. Recent investigations have shown an association between beta-blocker (BB) therapy and a reduction in risk-adjusted mortality within the first 90 days after hip fracture surgery. We hypothesized that preoperative, and continuous postoperative, BB therapy may also be associated with a decrease in mortality within the first year after hip fracture surgery. METHODS: In this retrospective cohort study, all adults who underwent primary emergency hip fracture surgery in Sweden, between January 1, 2008 and December 31, 2017, were included. Patients with pathological fractures and conservatively managed hip fractures were excluded. Patients who filled a prescription within the year before and after surgery were defined as having ongoing BB therapy. The primary outcome of interest was postoperative mortality within the first year. To reduce the effects of confounding from covariates due to nonrandomization in the current study, the inverse probability of treatment weighting (IPTW) method was used. Subsequently, Cox proportional hazards models were fitted to the weighted cohorts. These analyses were repeated while excluding patients who died within the first 30 days postoperatively. This reduces the effect of early deaths due to surgical and anesthesiologic complications as well as the higher degree of advanced directives present in the study population compared to the general population, which allowed for the evaluation of the long-term association between BB therapy and mortality in isolation. Results are reported as hazard ratios (HR) with 95% confidence intervals (CI). Statistical significance was defined as a 2-sided P value <.05. RESULTS: A total of 134, 915 cases were included in the study. After IPTW, BB therapy was associated with a 42% reduction the risk of mortality within the first postoperative year (adjusted HR = 0.58, 95% CI, 0.57–0.60; P < .001). After excluding patients who died within the first 30 days postoperatively, BB therapy was associated with a 27% reduction in the risk of mortality (adjusted HR = 0.73, 95% CI, 0.71–0.75; P < .001). CONCLUSIONS: A significant reduction in the risk of mortality in the first year following hip fracture surgery was observed in patients with ongoing BB therapy. Further investigations into this finding are warranted.